Simian immunodeficiency virus-specific cytotoxic T-lymphocyte induction through DNA vaccination of rhesus monkeys. - Yasutomi, Y (1996)
In view of the growing evidence that virus-specific cytotoxic T lymphocytes (CTL) play an important role in containing the early spread of human immunodeficiency virus type 1 (HIV-1) in infected individuals, novel vaccine strategies capable of eliciting HIV-1-specific CTL are being pursued in attempts to create an effective AIDS vaccine. We have used the simian immunodeficiency virus of macaques (SIVmac)/rhesus monkey model to explore the induction of AIDS virus-specific CTL responses by DNA vaccination. We found that the inoculation of rhesus monkeys with plasmid DNA encoding SIVmac Env and Gag elicited a persisting SIVmac-specific memory CTL response. These CTL were CD8+ and major histocompatibility complex class I restricted. These studies provide evidence for the potential utility of DNA inoculation as an approach to an HIV-1 vaccine.